English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

1. 12 - 6x = 18 - 7x

2. x + 3/4 = -9/2

3. 8 ( y + 3 ) =3(2y + 12)

4. x/2 + 2x/3 + 3 = x+3

5. x-2/3 - 4 = x +1/4

2007-10-05 08:24:18 · 6 answers · asked by Anonymous in Science & Mathematics Mathematics

6 answers

1. 12 - 6x = 18 - 7x
-6x+7x = 18-12
x = 6

2. x + 3/4 = -9/2
x = -9/2 -3/4 = -21/4

3. 8 ( y + 3 ) =3(2y + 12)
8y+24 = 6y +36
8y-6y = 36-24
2y = 12
y=6

4. x/2 + 2x/3 + 3 = x+3
3x +4x +18 = 6x+18
x = 0

5. (x-2)/3 - 4 = x +1/4 <-- I think you meant this
x-2 -12 = 3x +3/4
x-3x = 2+12+3/4
-2x = 14 3/4
x = - 7 3/8

2007-10-05 08:37:46 · answer #1 · answered by ironduke8159 7 · 0 0

1)7x-6x=18-12 => x=6
2)x=-9/2+3/4=-18/4+3/4=-15/4
3)8y+24=6y+36 => 2y=12 => y=6
4)?
5)?

2007-10-05 15:36:01 · answer #2 · answered by dumber 2 · 0 0

1. -6x + 7x = 18 -12
x = 6
2. x= -9/2 - 3/4
x = -5 1/4
3. 8y + 24 = 6y + 36
8y - 6y = 36 - 24
2y = 12
y = 6
4. 7x/6 - x = 3 -3
x/6 = 0
x = 0
5. x - 14/3 = x + 1/4
so there is an error in this one, maybe u typed it wrong

2007-10-05 15:32:02 · answer #3 · answered by dreamer 3 · 0 0

4. x/2 + 2x/3 + 3 = x+3
=> 3x + 4x + 18 = 6x + 18........X by 6
=> x = 0

2007-10-05 15:28:21 · answer #4 · answered by harry m 6 · 1 0

1. x = 6
2. x = 21/4
3. y = 6
4. x = 0
5. Impossible 0=59/12 ...

2007-10-05 15:30:24 · answer #5 · answered by pro 2 · 1 0

1. -6 = -13x

2. x = -21/4

3. y = 6

4. x/2 + 2x/3 = x

5. 4 11/12 = -1x

2007-10-05 15:30:15 · answer #6 · answered by Steve.WI 2 · 1 0

fedest.com, questions and answers